First report of Mycobacterium avium subsp. hominissuis in a black howler monkey (Alouatta caraya): a study with mycobacterial interspersed repetitive unit–variable number of tandem repeats genetic profiling - Didkowska Anna; Majchrzak Marta; Załuski Michał; Brzezińska Sylwia; Jańczak Dawid; Nowak Magdalena; Tchórz Wiktoria; Augustynowicz-Kopeć Ewa; Matusik Katarzyna; Parniewski Paweł (Journal of Veterinary Research, 2025)
Over the past three decades, emerging epidemiological evidence has shown the increasing incidence and prevalence of nontuberculous mycobacteria (NTM). As a result, clinical awareness of the impact these organisms have on both human and animal health has grown.